2018
DOI: 10.1287/isre.2017.0735
|View full text |Cite
|
Sign up to set email alerts
|

Copycats vs. Original Mobile Apps: A Machine Learning Copycat-Detection Method and Empirical Analysis

Abstract: While the growth of the mobile apps market has created significant market opportunities and economic incentives for mobile app developers to innovate, it has also inevitably invited other developers to create rip-offs. Practitioners and developers of original apps claim that copycats steal the original app’s idea and potential demand, and have called for app platforms to take action against such copycats. Surprisingly, however, there has been little rigorous research analyzing whether and how copycats affect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…Wen and Zhu () examine Google’s introduction of its own mobile apps for its Android system. Similar to Wang, Li, and Vir Singh (), they find that in each of the three entry events they studied, there are a large number of third‐party apps offering similar features. Because Google’s entry makes these markets less attractive for app developers, its entry pushes these app developers to innovate in other product spaces, which may reduce wasted efforts in developing these duplicate apps.…”
Section: Motivations For Platform‐owner Entrysupporting
confidence: 69%
“…Wen and Zhu () examine Google’s introduction of its own mobile apps for its Android system. Similar to Wang, Li, and Vir Singh (), they find that in each of the three entry events they studied, there are a large number of third‐party apps offering similar features. Because Google’s entry makes these markets less attractive for app developers, its entry pushes these app developers to innovate in other product spaces, which may reduce wasted efforts in developing these duplicate apps.…”
Section: Motivations For Platform‐owner Entrysupporting
confidence: 69%
“…In the same industry context, Massimino et al (2017) found that being located in a geographical area with many same-industry firms improved confidentiality; this finding, however, omits the impact of inter-organizational networks. Our study implies a need for heightened sensitivity to the dual nature of information and knowledge exposure (Niculescu, Wu, & Xu, 2018;Wang, Li, & Singh, 2018). Our second contribution relates to the understanding of structural holes during product development activities.…”
Section: Contributionsmentioning
confidence: 99%
“…This is not possible unless the digital firm deploys sufficient technological capabilities for creatively combining a huge variety of software components to upgrade the technology on multiple fronts. However, once a digital firm deploys adequate technological capabilities to evolve a technology as per the requirements of a heterogeneous lead market, the resulting technology may be difficult to imitate, which offers a lasting advantage against copycat apps and local clones across countries (Shaheer and Li 2020; Wang, Li, and Singh 2018).…”
Section: Theory and Hypothesesmentioning
confidence: 99%